The Effectiveness of the Cabri 3D Media-Assisted Deep Learning Approach in Learning Spatial Structures for Fifth Grade Elementary School Students - Desi Aryani Desi; Fifin Eka Yuliana; Pradista Selfia (Universitas PGRI Semarang, 2026)
This study aims to determine the effectiveness of the application of the Deep Learning approach assisted by Cabri 3D media in learning spatial geometry for fifth-grade students of SDN Karangsari 4. In this study, there was a low understanding of students on spatial geometry material due to the approach used in learning, namely the traditional teaching approach that does not involve students actively. The Deep Learning approach assisted by Cabri 3D media was applied as a solution, by emphasizing meaningful learning, mindful learning, and joyful learning. The method used was quantitative with a one-group pretest-posttest design. The research sample was 22 students of class VA. Data collection techniques included tests (pretest and posttest). Data analysis used was the normality test, homogeneity test, paired sample t-test and N Gain test. The results of the pretest value normality test obtained a sig value of 0.165, meaning the pretest value is normal, and the results of the posttest value normality test obtained a sig value of 0.194, meaning the posttest value is normal. Based on the results of the homogeneity test, a sig value of 0.926 was obtained, meaning the students' pretest and posttest values ​​were homogeneous. So both pretest and posttest values ​​were normally distributed. Based on the output results of the